Research in education - Best, John W. 4 0 16; Kahn, James V.; 5 (Boston : Pearson/Allyn and Bacon, 2006)
This text provides comprehensive coverage of research methods and statistics in a readable and student-friendly format. The authors address a wide variety of methodologies including descriptive, experimental and quasi-experimental research, historical studies, qualitative methods, and single subject designs. A complete range of research tools as well as descriptive and inferential statistics are also included, making this text the definitive resource for introductory research courses.--Jacket
Using research navigator -- pt. I. Introduction to educational research : definitions, research problems, proposals, and report writing -- 1. Fundamentals of research -- 2. Selecting a problem and preparing a research proposal -- 3. The research report -- pt. II. Research methods -- 4. Historical research -- 5. Descriptive studies : assessment, evaluation, and research -- 6. Experimental and quasi-experimental research -- 7. Single-subject experimental research -- 8. Qualitative research -- 9. Methods and tools of research -- pt. III. Data analysis -- 10. Descriptive data analysis -- 11. Inferential data analysis -- 12. Computer data analysis -- App. A. Statistical formulas and symbols -- App. B. Sample data Microsoft Excel format -- App. C. Percentage of area lying between the mean and successive standard deviation units under the normal curve -- App. D. Critical values for Pearson's product-moment correlation (r) -- App. E. Critical values of student's distribution (t) -- App. F. Abridged table of critical values for chi square -- App. G. Critical values of the F distribution.
Reprint. Singapore : Pearson Education South Asia, ©2007.
Includes bibliographical references and indexes.
Keywords: 2 -- 0; 6; Research. -- Education; 20; 2